The epidemic of Asian influenza in Poland, 1957 - Przesmycki, Felix (1959)
In 1957 the number of influenza cases began to rise above the inter-epidemic level in the 32nd week of the year in Katowice Province of Poland and in the 41st week in the majority of remaining provinces. The peak was reached between the 42nd and 45th weeks in the various provinces, in which the total epidemic lasted for periods varying from eight to 11 weeks. For the country as a whole, the main epidemic period was October-November. The clinical picture was generally rather mild, with very few serious cerebral symptoms and no complications of the peripheral nervous system. The epidemic appears to have caused no increase in the number of deaths from pneumonia in infants, but there was a slight increase among children of school age and a marked one among adults, for whom the figures for complications of all sorts were rather higher than in the previous influenza epidemics. Serological tests on paired human sera showed a marked increase in complement-fixing antibody in several. Haemagglutination-inhibition tests were carried out on both human and animal sera, negative results being obtained in almost all the latter. Nine influenza strains were isolated, identified as Asian influenza. Two of them showed a low avidity to the Singapore and other Asian immune sera.